(63x+50y)-(17x+35y)=

Simple and best practice solution for (63x+50y)-(17x+35y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (63x+50y)-(17x+35y)= equation:


Simplifying
(63x + 50y) + -1(17x + 35y) = 0

Remove parenthesis around (63x + 50y)
63x + 50y + -1(17x + 35y) = 0
63x + 50y + (17x * -1 + 35y * -1) = 0
63x + 50y + (-17x + -35y) = 0

Reorder the terms:
63x + -17x + 50y + -35y = 0

Combine like terms: 63x + -17x = 46x
46x + 50y + -35y = 0

Combine like terms: 50y + -35y = 15y
46x + 15y = 0

Solving
46x + 15y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15y' to each side of the equation.
46x + 15y + -15y = 0 + -15y

Combine like terms: 15y + -15y = 0
46x + 0 = 0 + -15y
46x = 0 + -15y
Remove the zero:
46x = -15y

Divide each side by '46'.
x = -0.3260869565y

Simplifying
x = -0.3260869565y

See similar equations:

| (64x+48y)-(9x-16y)= | | 5x-3=-10x+8 | | 2x+8=-28 | | (30+5x)+(15+10x)=180 | | 6x+5=9x-19 | | 64-7x=2x+17 | | 2x+3x+1=12-6 | | 6x+14=-40 | | 8-9[9-(3y-7)]= | | 6-9x=29-16x | | 61-7x=11x+23 | | 13-8x=39-22x | | 6-9x=29-6x | | x/2+1=5 | | 2(x-3)=-3x+4 | | 75.60=9x | | 21-2(3+5)= | | x=2(3s-8)+7 | | 4+10x=76+x | | 2x-3(2x-3)=2(3+2x)-13 | | 13x^2=4x-17 | | 7y+7=28 | | 3x+2y-1=8 | | 68-4=7x+24 | | -2y+6x=10 | | 7-4x=-5 | | 6x^2-3x-7=0 | | 12.5=x^2 | | 3t^2+5t-9=0 | | x^3-37x+6=0 | | 23t+5(1-5t)= | | 3t(3t)+5t-9=0 |

Equations solver categories